2017
DOI: 10.1155/2017/4802319
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Tumor Necrosis Factor-α-Induced Protein 8-Like 2 mRNA Is Negatively Correlated with Serum Concentrations of Tumor Necrosis Factor-α and Interleukin 6 in Type 2 Diabetes Mellitus

Abstract: Background Tumor necrosis factor-α-induced protein 8-like 2 (TIPE2 or TNFAIP8L2) is a negative regulator of natural and adaptive immunity. The role of TIPE2 in type 2 diabetes mellitus (T2DM) remains unknown, although TIPE2 plays key roles in preserving inflammatory homeostasis. Methods TIPE2 expression was measured by Western blotting and real-time polymerase chain reaction (RT-PCR) in peripheral blood mononuclear cells (PBMCs) isolated from T2DM patients and healthy controls, and tumor necrosis factor-α (TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These findings contradict the conventional notion that proinflammatory cytokines such as TNF-α and IL-6 contribute to insulin resistance. [16][17][18] Figure 1 Ratios of (A) TNF-α/IFN-γ and (B) IL-6/IFN-γ in 3-day PHA-induced PBMC cultures in the control and T2DM groups. PHA, phytohemagglutinin; T2DM, type 2 diabetes mellitus; PBMCs; peripheral blood mononuclear cells; TNF-α, tumor necrosis factor-α; IL-6, interleukin-6; IFN-γ, interferon-γ.…”
Section: Discussionmentioning
confidence: 99%
“…These findings contradict the conventional notion that proinflammatory cytokines such as TNF-α and IL-6 contribute to insulin resistance. [16][17][18] Figure 1 Ratios of (A) TNF-α/IFN-γ and (B) IL-6/IFN-γ in 3-day PHA-induced PBMC cultures in the control and T2DM groups. PHA, phytohemagglutinin; T2DM, type 2 diabetes mellitus; PBMCs; peripheral blood mononuclear cells; TNF-α, tumor necrosis factor-α; IL-6, interleukin-6; IFN-γ, interferon-γ.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that high levels of TNF-α is a crucial risk factor for diabetes (37). Furthermore, TNF-α is an important indicator of insulin resistance in obesity and may serve as a target for improving obesity-induced insulin resistance in patients with type 2 diabetes (38). Leptin, first discovered by Zhang et al in 1994, is a hormone that is secreted from adipose tissues and circulates in the blood (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, mostly in in vitro or murine experiments, found that exposure to tumor cells cause TAMs to shift to glycolysis with a more immunosuppressive phenotype. These TAMs secrete lactate, TNF and IL6 (48)(49)(50). Moreover, the canonical markers of M1 or M2 activation can be co-expressed by TAMs (43), explaining the conflicting studies on TAM metabolism within the TME.…”
Section: Metabolomics Of Innate Immunity Tumor-associated Macrophagesmentioning
confidence: 99%